Barriers and facilitators to attending pre‐pregnancy care services: the ATLANTIC‐DIP experience. Issue 3 (17th January 2014) - O'Higgins, S.; McGuire, B. E.; Mustafa, E.; Dunne, F.
Abstract Aims Pre‐pregnancy care programmes can help to reduce morbidity and mortality associated with pregnancy in women with diabetes. However, uptake of a free pre‐pregnancy care programme along the Irish Atlantic seaboard was only 30%. This study sought to better understand why women with diabetes mellitus (Type 1 and Type 2) choose to attend pre‐pregnancy care services and to identify perceived barriers to attendance. Methods A participative health research method called the participative research process was used to facilitate 14 women with diabetes mellitus to create 'webs of ideas' on the reasons for attendance and non‐attendance at a pre‐pregnancy care programme, and potential solutions for each obstacle. Results The participants identified information on the risks of pregnancy as crucial for all childbearing women with diabetes, as lack of information was a major obstacle to attendance at pre‐pregnancy care programmes. Practical constraints such as childcare difficulties and work commitments were also identified. Participants stressed that health practitioners need to focus on positive aspects of pregnancy and childbearing rather than focusing solely on the problematic aspects for women with diabetes mellitus. Conclusions Women with diabetes need support and reassurance about their ability to control blood glucose and have a successful pregnancy while coping with the multiple challenges inherent in diabetes management and pregnancy. To increase uptake of pre‐pregnancy care, a norm needs to be established that situates pre‐pregnancy care as something every woman with diabetes will do, whether or not she is actively contemplating becoming a mother at the time. Active use of social media and facilitating peer support should be encouraged in pre‐pregnancy services to facilitate attendance. The time has come to incorporate the skills of a clinical psychologist in the delivery of a pre‐pregnancy service.